Identification of class II ADP‐ribosylation factors as cellular factors required for hepatitis C virus replication. (25th February 2016) - Farhat, Rayan; Séron, Karin; Ferlin, Juliette; Fénéant, Lucie; Belouzard, Sandrine; Goueslain, Lucie; Jackson, Catherine L.; Dubuisson, Jean; Rouillé, Yves
Summary: GBF1 is a host factor required for hepatitis C virus (HCV) replication. GBF1 functions as a guanine nucleotide exchange factor for G‐proteins of the Arf family, which regulate membrane dynamics in the early secretory pathway and the metabolism of cytoplasmic lipid droplets. Here we established that the Arf‐guanine nucleotide exchange factor activity of GBF1 is critical for its function in HCV replication, indicating that it promotes viral replication by activating one or more Arf family members. Arf involvement was confirmed with the use of two dominant negative Arf1 mutants. However, siRNA‐mediated depletion of Arf1, Arf3 (class I Arfs), Arf4 or Arf5 (class II Arfs), which potentially interact with GBF1, did not significantly inhibit HCV infection. In contrast, the simultaneous depletion of both Arf4 and Arf5, but not of any other Arf pair, imposed a significant inhibition of HCV infection. Interestingly, the simultaneous depletion of both Arf4 and Arf5 had no impact on the activity of the secretory pathway and induced a compaction of the Golgi and an accumulation of lipid droplets. A similar phenotype of lipid droplet accumulation was also observed when GBF1 was inhibited by brefeldin A. In contrast, the simultaneous depletion of both Arf1 and Arf4 resulted in secretion inhibition and Golgi scattering, two actions reminiscent of GBF1 inhibition. We conclude that GBF1 could regulate different metabolic pathways through the activation of different pairs of Arf proteins.